Gender in law - Ahmad, Tahmina; Khan, Maimul Ahsan (Dhaka : Adtam Pub. House, 1998)
With reference to Bangladesh.
Includes bibliographical references.
Keywords: Women (Islamic law) -- Bangladesh; Sex and law -- Bangladesh